The environmental benefit of Beijing-Tianjin-Hebei coal banning area for North China. (1st June 2022) - Si, Ruirui; Xin, Jinyuan; Zhang, Wenyu; Tian, Yongli; Xu, Xiaojuan; Wen, Tianxue; Ma, Yining; Ma, Yongjing; Cao, Yukun; Liu, Zirui; Wang, Yuesi; Wang, Lili; et al.
Abstract: In order to achieve the targets specified in the Action Plan for Air Pollution Prevention and Control (APAPPC), a limited coal banning area (10, 000 km 2 ) was designated in the heavily polluted Beijing-Tianjin-Hebei region (BTH) for the first time in 2017. PM2.5 and elements were sampled by the network of BTH to evaluate the effectiveness of this policy. This study found that the fine days with PM2.5 < 75 μg m −3 accounted for 74.3% in the autumn and winter of 2017, which was significantly higher than that in 2016 (43%). The heavily polluted days (PM2.5  > 150 μg m −3 ) also decreased from 32.2% in 2016 to 4.9% in 2017. Arsenic (As) is an important tracer in coal consumption, which can be used to reflect the influence of the establishment of coal banning areas on north China. The cluster analysis of air mass forward trajectory identified that the number of polluted trajectories with PM2.5 and As in 2017 decreased by 47.6% and 49.7%, respectively. Under the implementation of the coal banning policy, the weighted concentration of PM2.5 and As decreased by 94.2 μg m −3 and 5.1 ng m −3 in the coal banning area, 60.9 μg m −3 and 3.4 ng m −3 in the no coal banning area in BTH, respectively. The influence of weighted concentration of PM2.5 and As in coal banning area on North China were 1.6–49.2 μg m −3 and 0.15–2.8 ng m −3, respectively, which was 38.8% and 29.7% lower than 2016. In coal banning area, BTH and other parts of North China, the reduction of the weight concentration of PM2.5 in 2017 accounted for 41.4%, 26.8% and 31.8% of the total reduction, respectively, so was the As in 39%, 26.3% and 34.6%, indicating that setting up a coal banning area scientifically in limited areas can produce remarkable regional benefit. Graphical abstract: Image 1 Highlights: Coal banning area brought remarkable environmental benefit to the whole north China. Fine days in the autumn and winter of BTH increased from 43% in 2016 to 74% in 2017. Impact of PM2.5 in coal banning area (BTH) reduced by 94.2 (60.9) μg m −3 in 2017. The impact of coal banning area on PM2.5 in North China decreased by 48.3% in 2017.